MODEL PERENCANAAN PENGEMBANGAN WILAYAH KEPULAUAN NUSA TENGGARA - HARUN, UTON RUSTAN (Program Studi Perencanaan Wilayah dan Kota, UPT Publikasi Publikasi Ilmiah UNISBA, 2010)
Indonesia has over 17,000 islands and long coastline which reached 81,000 km, is the largest archipelagic country in the world. However, the model-oriented development planning ke-kontinen/daratan territory, is still very limited for developing model-based development of the islands of maritime (maritime). Entanglement one island to another island in one unified remote islands naturally built olehhubungan functional ecosystem. During these activities the layout, planning area boundaries using administrative boundaries and functional social-economic development. So that spatial relationships without regard Kepuluan ecosystem. The result is the development of socio-economic inequality of small islands than large islands are reflected from poverty and backwardness of eastern Indonesia this paper - which was based on the use of Dynamic Simulation Model - trying to prove the importance of the spatial arrangement of the islands based on ecosystem boundaries (known as Ecoregion). At various scenarios simulated spatial models based approach to development since the scenario based on current (status quo approach to administrative boundaries) to the scenario based on the sustainable development approach (approach Ecoregion). The results show that an effort to manage the large island had a significant impact on the growth of social, economic and environment on the other islands in the archipelago cluster units. Furthermore, note also influential factors to be considered in a spatial concept berkawasan coastal islands Ecoregion approach.